Strategi Komunikasi Guru BK Terhadap Kenakalan Siswa di MAN 1 Sumbawa - Alan Nur Akbar; Aka KurnianSF (Universitas Katolik Widya Karya Malang, 2023)
Students in adolescence often commit various kinds of troubling delinquencies and lately through various kinds of mass communication tools, the problem of juvenile delinquency has become an object of discussion. Delinquency in students occurs because of the unstable condition of students or can also be influenced by their environment, both from the family environment, friendships, and the community environment. Realizing this, guidance and counseling teachers are required to overcome the problem of deviant behavior of students, because education is seen as one aspect that has an important role in shaping the mentality of future generations. The purpose of this research is to find out the communication strategy of counseling teachers against student delinquency at MAN 1 Sumbawa. The research method used in this research is a qualitative research approach that is qualitative-descriptive in nature, namely a study that describes and describes a problem. Data collection techniques are observation, interviews and documentation. Data is analyzed interactively with the steps of data reduction, data presentation and conclusion drawing. The results of this study are communication strategies carried out by counseling teachers, namely 1) Conducting guidance and direct approach to problem students. 2) directing students to take part in positive activities such as extracurricular activities and religious activities so that students do not do negative things. 3) The imposition of sanctions on students who commit violations. So that it is hoped that no further violations will occur and have a deterrent effect on students. The forms of sanctions imposed do not lead to negative things, but lead to positive actions from the effects of these sanctions.